2006
DOI: 10.1111/j.1574-6968.1997.tb10442.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Saccharomyces cerevisiae defective in vacuolar function confirm a role for the vacuole in toxic metal ion detoxification

Abstract: To directly define vacuolar role(s) in metal detoxification, we have examined the responses of vacuole-deficient mutants of Saccharomyces cerevisiae to several potentially toxic metals known to be mainly detoxified in the cytosol (Cu, Cd) or the vacuole (Co, Mn, Ni, Zn). Three mutants, deficient in targeting of vacuolar proteins, were used with JSR18 delta 1 being devoid of any vacuole-like structure while ScVatB and ScVatC were deficient in specific protein subunits of the V-ATPase. The results obtained show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…However, research demonstrations have shown that, the intracellular accumulation of these cations beyond certain physiological limit turn to impact negatively (metal ion toxicity) on fungal growth and development. Sequestering activities of the vacuole play an important role in shielding cells from the harmful effects of toxic metal ions and also crucially mediate the detoxification of these metal ions (Ramsay and Gadd, 1997). To examine the contribution of MoVps41 in vacuolar sequestering and subsequent detoxification of metal ions, we monitored the vegetative growth ΔMovps41 mutant, Guy11 wild-type and the C-21 complemented strain on 1/4 YG growth medium supplemented with defined concentration of divalent metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…However, research demonstrations have shown that, the intracellular accumulation of these cations beyond certain physiological limit turn to impact negatively (metal ion toxicity) on fungal growth and development. Sequestering activities of the vacuole play an important role in shielding cells from the harmful effects of toxic metal ions and also crucially mediate the detoxification of these metal ions (Ramsay and Gadd, 1997). To examine the contribution of MoVps41 in vacuolar sequestering and subsequent detoxification of metal ions, we monitored the vegetative growth ΔMovps41 mutant, Guy11 wild-type and the C-21 complemented strain on 1/4 YG growth medium supplemented with defined concentration of divalent metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…S3). It has been well established in yeasts and plants that the vacuole is the primary organelle for accumulation and detoxification of metal ions (Ramsay and Gadd, 1997;Tong et al, 2004). In this respect, smaller vacuoles in ΔMrpacC could account for its reduced ability for ion tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The first clues implicating the role of vacuoles in metal-ion homeostasis came with genetic studies utilizing yeast strains defective in vacuolar biogenesis and function; these strains exhibited growth defects when exposed to a host of transition metal salts, including cobalt, manganese, iron, nickel, copper, zinc, and cadmium 85,86. Indeed, manganese is more concentrated in the vacuole than in the cytosol, thereby providing a site with which to sequester toxic excess levels of cellular manganese that can potentially wreak havoc in a variety of cellular compartments 6,86,87. Thus far, one vacuolar manganese transport pathway has been definitively identified, Ccc1p 6,88,89.…”
Section: Vacuolar Manganese Transporter Ccc1pmentioning
confidence: 99%